صورة الحيوان في الأمثال الشعبية السوفية دراسة موضوعاتية - اللبي, نور الهدى; ودات, هنية (جامعة الوادي - university of Eloued, 2023)
تهدف هذه الدراسة إلى محاولة بيان ما استقر في الذاكرة الشعبية السوفية من أمثال جسدت صورا لتلك المخلوقات التي استأنسها السوفي، ومن خلال جمعنا للمادة الشعبية التي كان الحيوان محورها الأساسي والذي كان حاضرا في شتى موضوعاتها، لاحظنا أن الأمثال الشعبية لم تترك خُلقا أو موضوعا أو سلوكا خاصا بالفرد داخل الوسط الذي يعيش فيه، لأن صلاح الفرد يؤدي بالضرورة إلى صلاح الأمة، فالأمثال تصور النضوج الفكري والأخلاقي لهاته الأخيرة فهي بمثابة قواعد وقوانين هدفها تنظيم سلوك الفرد وضبطه داخل الحياة الاجتماعية، وهذه المواضيع صنفنا فيها أمثالا صورت الحيوان حسب الموضوع الذي تنتمي إليه، ومن المواضيع التي تطرقنا إليها هي كالآتي: موضوع الدين، الموضوع الاجتماعي الموضوع الأخلاقي، الموضوع الاقتصادي. حاولنا جمع ما أمكن من الأمثال الشعبية المحلية لوادي سوف وتصنيفها مع شرحها حسب الموضوع الذي تنتمي إليه. This study aims to try to show what settled in the alsoufi popular memory of the proverbs embodied images of those creatures that were domesticated by the Sufi, and through our collection of popular material that was the animal the main axis and which was present in various topics, we noticed that the proverbs did not leave a creation or subject or behavior of the individual within the center in which he lives, because the goodness of the individual necessarily leads to the goodness of the nation, The proverbs depict the intellectual and moral maturity of the latter, as they serve as rules and laws aimed at regulating the behavior of the individual and controlling it within social life, and these topics we classified in them proverbs portrayed the animal by subject belong to it, and the topics that we touched on are as follows: the subject of religion, the social subject, the moral subject, the economic subjec We tried to collect as much as possible from the local folk proverbs of oued souf and classify them with explanations according to the topic to which they belong.
أدب شعبي
Keywords: المثل، الحيوان، الموضوع; Example, animal, Subject